(untitled) (Nueva Epoca, 2020)
This article takes as its starting point the analytical distinction between the recomposition/repair, prevention, and precaution functions to carry out a study of the preventive function. In particular, judicial decisions that have resolved preventive actions in relation to different issues associated with environmental risks and damages are analyzed.